Wheat (Triticum aestivum L.) production faces challenges caused by abiotic and biotic factors, with diseases transmitted by contaminated seeds being a risk for pathogen-free areas. This study assessed the presence of pathogens in five wheat cultivars: Tbio Sinuelo, Tbio Toruk, ORS Madreperola, Tbio Ponteiro and LG Cromo. The “blotter test” method was used to assess the influence of these pathogens using the Hiltner test. The following variables were analyzed in seeds disinfected and not disinfected with 1% hypochlorite: germination (%), seed-to-seedling transmission, mean root length (MRL), mean shoot length (SPL), root fresh mass (RRM), root dry mass (RSM), shoot fresh mass (SPF) and shoot dry mass (SPD). The experiment, conducted at the Plant Physiology Laboratory of the Federal University of the Southern Frontier, followed a completely randomized design in a 5x2 factorial scheme. The sanitary analysis revealed the presence of the genera Fusarium, Aspergillus, Penicillium, Rhizopus and Alternaria. Although germination and seed-to-seedling transmission showed no significant difference between disinfected and non-disinfected seeds, there were statistical differences in the ARL, SPL, FRM, DRM, FRM and DSM components, with disinfected seeds showing higher averages. (Colloquium Agrariae. ISSN: 1809-8215, 2025)
Wheat (Triticum aestivum L.) production faces challenges caused by abiotic and biotic factors, with diseases transmitted by contaminated seeds being a risk for pathogen-free areas. This study assessed the presence of pathogens in five wheat cultivars: Tbio Sinuelo, Tbio Toruk, ORS Madreperola, Tbio Ponteiro and LG Cromo. The “blotter test” method was used to assess the influence of these pathogens using the Hiltner test. The following variables were analyzed in seeds disinfected and not disinfected with 1% hypochlorite: germination (%), seed-to-seedling transmission, average root length (ARL), average shoot length (SPL), fresh root mass (FRM), dry root mass (DRM), fresh shoot mass (FRM) and dry shoot mass (DSM). The experiment, conducted at the Plant Physiology Laboratory of the Federal University of the Southern Frontier, followed a completely randomized design in a 5x2 factorial scheme. The sanitary analysis revealed the presence of the genera Fusarium, Aspergillus, Penicillium, Rhizopus and Alternaria. Although germination and seed-to-seedling transmission showed no significant difference between disinfected and non-disinfected seeds, there were statistical differences in the ARL, SPL, FRM, DRM, FRM and DSM components, with disinfected seeds showing higher averages.